PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020) - Marcelleo, Hanshen; Panjaitan, Fery; Astuti, Nelly (Jurnal Progresif Manajemen Bisnis, 2021)
The title of this thesis in Bahasa Indonesia : "Pengaruh Penerapan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan (Studi Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020)". The research conducted from February 2020 to July 2020, it consists of 129pages without attachments. The purpose of this study was to determine the effect of the implementation of good corporate governance on the company’s financial performance (Study on Pharmaceutical Companies Listed on the Indonesia Stock Exchange. The theory used in this research is Management theory, Financial Management theory, Good Corporate Governance theory. The method used in this study is descriptive with a quantitative approach with a view to finding the relationship between the independent variable and the dependent variable by using a statistical formula that examines the relationship between the implementation of good corporate governance on the company’s financial performance (Study on Pharmaceutical Companies Listed on the Indonesia Stock Exchange. Meanwhile, The statistical formula used to test the hypothesis is Multiple Linear Regression Analysis.The sample in this study amounted to 8 companies from 8 companies in the pharmaceutical sector listed on the Indonesia Stock Exchange, so it is better to take all so that the study is a population study. Based on the results of the study, it is shown that: (1) there is an insignificant effect between institutional ownership on financial performance, this is evidenced by the value of t-count < t-table (-0.845 > 1.70329). (2) There is an insignificant effect between managerial ownership on financial performance, this is evidenced by the value of t-count < t-table (-0.776 > 1.70329). (3) There is an insignificant effect between independent commissioners on financial performance, this is evidenced by the value of t-count < t-table (0.677 > 1.70329). (4) There is an insignificant effect between the audit committee on financial performance, this is evidenced by the value of t-count < t-table (0.250 > 1.70329). (5) The results showed that there was an insignificant effect between institutional ownership, managerial ownership, independent commissioners and audit committees on financial performance as evidenced by the F-count > F-table (0.359 > 2.73).